دراسة التشوهات اللاخطية في التلفزيون وتصحيحها - عيسى, سمير; الكنا, ميساء; مقصود, سميرة; عثمان, فاطمة (Latakia University Journal -Engineering Sciences Series, 2019)
هذا البحث يعتمد على تصحيح التشوهات اللاخطية للإشارة التلفزيونية والحصول على الشكل المناسب لخواص إرسال مستويات النصوع في النظام التلفزيوني، حيث تحدث تلك التشوهات اللاخطية للإشارة التلفزيونية في محولات ضوء ـ إشارة ومحولات إشارة ـ ضوء وفي مراحل المكبر الأولي لإشارة الصورة وذلك بسبب لاخطية خواصها الضوئية والمطالية، وتؤدي هذه التشوهات إلى الحصول على إنتاج غير صحيح لتدرجات النصوع على شاشة جهاز الاستقبال للصورة التلفزيونية المرسلة, وتسبب هذه التشوهات في أنظمة التلفزيون الملون تشويه الألوان. وسوف ندرس تصحيح تشوهات النصوع للصورة بتغيير قيمة التشوهات اللاخطية للإشارة التلفزيونية بواسطة ما يسمى مصحح الغاما, ثم نضع الدارة العملية لهذا المصحح، ونحدد شكل الخواص المطالية، وقد اخترنا الدارة المناسبة لبناء الخواص المطالية النموذجية لمصحح الغاما. This paper depends on the correction of non-linear distortions for television signal to get the appropriate form for the transmission properties of luminance levels in TV system, whereas these non- linear distortions of television signal occur in light-signal transformers and signal-light transformers and in the preamplifier stages of image signal because of non- linear photo and amplitude characteristics. These distortions result in impaired reproduction of the gradations of luminance in transmitted television picture, and they cause chromaticity impairment in color TV systems, so in our research we'll study the correction of luminance of image by changing the value of non-linear distortions of TV signal by so-called Gamma Corrector, then we put the process circuit and determine the amplitude properties form . We select the suitable circuit for this correction then we build the model amplitude properties for Gamma Corrector.